Pyoderma gangrenosum associated with Behçet's disease - Sertaç KETENCİ,; Ender SALBAŞ, (Archives of Rheumatology, 2021)
A 26-year-old female patient was diagnosed with Behçet’s disease in an off-center clinic due to the complaints of oral aphthae, genital ulceration, erythema nodosum, pathergy and human leukocyte antigen-B51 positivity. Her complaints decreased following treatment with colchicine and methylprednisolone. After a one-year interval without treatment, she was diagnosed as soft tissue infection on the front side of the leg. As there was no response to the intravenous (IV) antibiotherapy on the fifth day, a consultation was sought from the rheumatology department. In the examination, highly painful ulcerative lesions were considered to be a potential case of pyoderma gangrenosum (Figure 1a and b). Active oral aphthae and genital ulceration were also detected. The erythrocyte sedimentation rate was 110 mm/hour. Symptoms were not compatible with inflammatory bowel disease. In the dermis biopsy, severe mixed- type perivascular inflammatory reaction and focal abscess formation were reported, which was in line with the pyoderma gangrenosum diagnosis. After a three-day 100 mg/day IV methylprednisolone administration, 48 mg/day methylprednisolone and azathioprine 100 mg/ day orally were initiated. Her ulcerative lesions started to heal and acute phase responses began to normalize. <f1> Very few cases of pyoderma gangrenosum associated with Behçet’s disease are available in the literature.[1] In the identified cases, mostly intestinal involvement of Behçet’s disease is observed.[2] In our case, a pyoderma gangrenosum during the course of isolated mucocutaneous Behçet’s disease was detected. While pyoderma gangrenosum is often associated with inflammatory bowel diseases, rheumatoid arthritis and vasculitis, conditions such as oral aphthae and genital ulceration, which may be overlooked, must be kept in mind and a potential Behçet’s disease should not be ignored.